2018
DOI: 10.1039/c8ob00790j
|View full text |Cite
|
Sign up to set email alerts
|

A “cross-stitched” peptide with improved helicity and proteolytic stability

Abstract: A new computational approach to obtain quantitative energy profiles for helix folding was used in the design of orthogonal hydrocarbon and lactam bicyclic peptides. The proteolytically stable, "cross-stitched" peptide SRC2-BCP1 shows nanomolar affinity for estrogen receptor α and X-ray crystallography confirms a helical binding pose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
30
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 29 publications
(19 reference statements)
0
30
1
Order By: Relevance
“…B) Short‐range n→π* interactions (blue arrows) reported between backbone carbonyls in a protein α‐helix. C) The crystal structure (PDB ID: 5wgd) shows a peptide (green) bound to estrogen receptor α in an α‐helical conformation (yellow) that is constrained by a cyclic pentapeptide component, and key features include: i) a water molecule (red) hydrogen bonded to the amide linker (dash), ii) a long‐range n→π* interaction from the backbone CO to a side‐chain carbonyl carbon (red arrow), and iii) angles ( θ =97°, Θ =1.5°) and distance ( d =3.10 Å) indicating amide pyramidalization.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…B) Short‐range n→π* interactions (blue arrows) reported between backbone carbonyls in a protein α‐helix. C) The crystal structure (PDB ID: 5wgd) shows a peptide (green) bound to estrogen receptor α in an α‐helical conformation (yellow) that is constrained by a cyclic pentapeptide component, and key features include: i) a water molecule (red) hydrogen bonded to the amide linker (dash), ii) a long‐range n→π* interaction from the backbone CO to a side‐chain carbonyl carbon (red arrow), and iii) angles ( θ =97°, Θ =1.5°) and distance ( d =3.10 Å) indicating amide pyramidalization.…”
Section: Figurementioning
confidence: 99%
“…The root mean square fluctuation (RMSF) for 1 was less than for 2 , 3 or 5 in water, and less than for 1 in DMSO, which is consistent with structure stabilization by water solvation. A crystal structure for estrogen receptor α bound to a peptide containing the same Lys i to Asp i +4 linker as in 1 and 6 showed two peptides crystallized in the unit cell; an α‐helical one with a water H‐bonded to the linker amide C γ =Ο (Figure C), and a less helical one with no crystallized water (Figure S20). When the linker amide was water‐solvated (Figure C), it was pyramidalized with a long‐range n→π* interaction as in 6 but with a shorter distance d= 3.10 Å.…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…GTP-ase [38], HIV-1 [39], Respiratory Syncytial Virus Entry [40,60], Ral GTP-ase [61], estrogen receptor-α [62] and BCL9 [63]. All these peptides exhibited increased helicity, increased proteolytic resistance and increased binding as compared to the corresponding single stapled peptides.…”
Section: Several Double-stapled Peptides Have Been Shown To Successfumentioning
confidence: 99%
“…However the double-stapled peptide d PMI-δ(1-5,9-12) didn't have significant cellular activity with an EC50 of 34.6 µM, at 16 hrs [ Figure 8, Table 2]. Although recent studies have reported that the double-stapled peptides appear to follow the same trend as their single-stapled counterparts [ 38,39,40,[60][61][62], lack of cell activity observed for the double-stapled peptide here, demonstrate that enhanced cellular activity is not uniform. Although the molecular 13 mechanisms behind the increased cell permeability of the stitched D-peptide is unclear, it could be attributed to the increased conformational rigidity and/or increased hydrocarbon content of the peptide.…”
Section: Several Double-stapled Peptides Have Been Shown To Successfumentioning
confidence: 99%